Rancang Bangun Aplikasi Pelaporan Tracer Study alumni Pada SMK Ketintang Surabaya - Bagus Mardianto; Sulistiowati sulistiowati; Norma Ningsih (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
SMK Ketintang is one of the vocational high schools in Surabaya, there is a problem, namely to collect alumni data which is still done manually. In carrying out the recording, there is often a buildup of registration forms because employees have to input one by one and the data collection process takes a long time. In sending data, there can be delays in sending alumni data to DISNAKER. As a result of collecting student data, which takes a long time, the impact on the data collection and collection process takes a long time. risk of experiencing delays. Based on the existing problems, a solution was obtained in the form of a Tracer Study reporting application. Tracer study reports include student data collection, delivery deadlines, the number of students who have done online data collection and those who have not. This research uses the System Development Life Cycle (SDLC) method in developing a tracer study reporting application. From the reporting results, it can be concluded that the application can send tracer study progress and alumni data output results.